2012
DOI: 10.3892/or.2012.2051
|View full text |Cite
|
Sign up to set email alerts
|

A new purification method for enhancing the immunogenicity of heat shock protein 70-peptide complexes

Abstract: When purified from a tumor, certain heat shock protein 70 (HSP70)-peptide complexes (PCs) can function as effective vaccines against the tumor from which the complexes were isolated. The immunogenic mechanisms of HSP70 preparations imply that tumor-derived HSP70-PCs exhibit antigens associated with antigen-presenting cells such as dendritic cells (DCs), inducing antigen-specific cytotoxic CD8+ T cells. However, some important membrane-resident tumor-associated peptides, such as the HER-2/neu (c-erbB2) oncogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…Early studies revealed many important antigens in human tumor cell lines. They used lysates of human tumor cell lines to pulse DCs for treatment of the same kind of tumor and achieved a certain therapeutic effect ( 4 , 12 , 13 , 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early studies revealed many important antigens in human tumor cell lines. They used lysates of human tumor cell lines to pulse DCs for treatment of the same kind of tumor and achieved a certain therapeutic effect ( 4 , 12 , 13 , 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study revealed that HSP70-PCs purified from tumor cells have better immunocompetence than lysates of the same cells. Moreover, we established a new method using the detergent CHAPS to purify HSP70-PCs containing more efficient tumor peptides from human cancer cells ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some alternatives have been tested, including HSPs-pulsed dendritic cells[ 15 ], chaperone-rich cell lysates derived from tumors(CRCL) [ 23 ], combination with GM-CSF [ 18 , 24 ], recombinant HSPs with tumor-associated peptides[ 25 ] or encapsulated in nanoemulsions [ 26 ] and have shown improved immunogenicity. Furthermore, improved antitumor immune responses have been observed following the development of specific new methods of vaccine preparation for enhanced immunogenicity[ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%